"Integrity matters : an inquiry into social workers' understandings" : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Social Work, School of Health and Social Services, Massey University, Palmerston North, New Zealand - Appleton, Cherie May (Massey University, 2010)
This small scale study recruited a sample of qualified and experienced social work practitioners to explore the research question: “How do social workers in Aotearoa New Zealand perceive, understand and interpret the concept of integrity and how do they assess it as being relevant in their work?” The aim of this research was to capture and reflect the participants’ voices in relation to their perceptions, appreciation and application of the notion of integrity to their work. The reasons for choosing to interrogate the topic of integrity were three-fold: i) I was intrigued with the word ‘integrity’ which I perceived to be much used and rarely defined or contextualised in social work conversations, Codes of Ethics and Codes of Conduct. ii) I suspected that the term ‘integrity’ could be a container or integrating concept for a range of values and virtues such as respect, dignity, spirituality, trustworthiness. iii) I wondered if in the process of discovering the practitioner voices in relation to integrity we might also reveal factors or processes that could strengthen critical reflection, enhance job satisfaction, and increase resilient practice. Beginning with an e-survey, participants identified and described some of their definitions and key concepts in relation to integrity. The e-survey provided material that was used in subsequent focus group interviews to further explore participants’ understandings and experiences of integrity. The data collected from the focus group interviews then underwent a thematic analysis and coding process. Findings from this process were distilled and collected under two main headings: Practitioners ‘constructing’ integrity and practitioners ‘maintaining’ integrity. Several themes such as practitioners ‘making meaning’ of integrity, professional and personal integrity, integrity in the workplace, practitioners ‘doing’ integrity and practitioners experiencing challenges to integrity were identified and explored. The discussions and conclusions reached as a result of this study contribute to the advancement of social work knowledge and offer social work practitioners a perceptive framework for enhanced professional reflexivity around constructing and measuring integrity with the possibility of balancing and strengthening integrity in their practice.
Keywords: Social workers; Professional ethics; New Zealand